Severity and Incidence of Spodoptera frugiperda Attack on Maize Plants in Sleman District - Alek Firnanda Aditia; Ichsan Luqmana Indra Putra (Institut Pertanian Bogor, 2025)
Spodoptera frugiperda (Lepidoptera: Noctuidae) is an invasive pest of maize that has caused damage and economic losses to maize crops in Indonesia. Damage caused by its larvae can be seen from the incidence and level of damage to maize plants, especially in the leaves. This study aimed to analyze the severity and incidence of S. frugiperda larvae infestation on maize plants in Sleman Regency. The study was conducted on the vegetative phase of maize plants in Sleman District. Sampling locations were determined using the survey method, and the fields were using the stratified scheme. The maize fields used for sampling were decided by a purposive method. Calculation of incidence and damage level was done using the letter W scouting procedure. Data was analyzed with a correlation test to see the relationship between damage level and S. frugiperda incidence in the district. The highest damage level was found in Ngaglik Subdistrict with 51 infested plants with high damage, while the lowest was found in Minggir Subdistrict with 179 infested plants with low damage. The highest incidence rate was found in Seyegan (47.55%), and the lowest in Minggir Subdistrict (11.96%). The conclusion of this study is that S. frugiperda infestation has been found in Sleman Regency with low to severe infestation, while the incidence rate is low to moderate. Keywords: Maize, occurrence, severity, Sleman, Spodoptera frugiperda